Multiple plaque incisions with or without grafting for Peyronie's disease. Issue 3 (12th January 2022) - Hegarty, Paul K.; O Sullivan, Daniel; Hegarty, Penelope A.; Zafirakis, Helen
Abstract: Objectives: To assess novel surgical techniques in management of Peyronie's disease. Subjects: Forty‐three men underwent corrective surgery using either partial plaque incision and nongraft (PPING) or multiple plaque incisions and graft (MPIG). The technique used was determined intra‐operatively. Patients were assessed at baseline and follow‐up based on Peyronie's disease questionnaire patient‐reported outcome measure (PDQ‐PROM) and erectile function. Results: The two groups were well matched in age and erectile function. At baseline MPIG group had greater deformity and poorer patient‐reported outcome. Penile curvature improved from 67.9° to 10.5° in the PPING group and 77.9° to 7.1° with MPIG. PDQ‐PROM improved from 29 to 13 in those who underwent PPING and 38.5 to 17.6 in those undergoing MPIG. Erectile function was preserved in both groups. Conclusions: These novel surgeries are effective in restoring penile shape and length while preserving erectile function. This is reflected in improved patient‐reported outcomes. These findings should be verified by multi‐institutional study.